1986
DOI: 10.1104/pp.82.4.1031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Shock on the Metabolism of Glutathione in Maize Roots

Abstract: ABSTRACT?High performance liquid chromatography analyses revealed that glutathione (GSH) and cysteine are two of the major low molecular weight thiol compounds in maize root extracts. Treatment of maize roots to heat shock temperatures of 40°C resulted in a decrease of cysteine levels and an increase of GSH levels. Pulse labeling of maize roots with [5Sjcysteine showed that the rate of incorporation of 3"S into GSH or glutathione disulfide (GSSG) in heat shocked tissues was twice that in nonheat shocked tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…Heavy metals have also been shown to stimulate the synthesis of phytoalexins in soybean cotyledons (17), and the effects of GSH on plant defense gene expression suggest a possible mechanism. Moreover, GSH plays a protective role in cellular metabolism by acting as a reductant to remove free radicals (16,20), and it has recently been shown that heat shock of maize roots elevates the cellular concentration of GSH (18). Oxidative reactions such as the release of superoxide anions and the peroxidation of lipids are early responses to mechanical damage and infection (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals have also been shown to stimulate the synthesis of phytoalexins in soybean cotyledons (17), and the effects of GSH on plant defense gene expression suggest a possible mechanism. Moreover, GSH plays a protective role in cellular metabolism by acting as a reductant to remove free radicals (16,20), and it has recently been shown that heat shock of maize roots elevates the cellular concentration of GSH (18). Oxidative reactions such as the release of superoxide anions and the peroxidation of lipids are early responses to mechanical damage and infection (4).…”
Section: Methodsmentioning
confidence: 99%
“…Functions proposed for glutathione in higher plants include: storage and transport of reduced sulfur; protein reductant; destruction of H202 in chloroplasts, and detoxification of xenobiotics including certain herbicides and pesticides (8,20). Overall, glutathione appears to play a key role in protection against oxidative damage arising from a number of stresses such as irradiation (16), heat (18), and exposure to heavy metals (10).…”
mentioning
confidence: 99%
“…Ozone, along with other oxidative stresses (sulphur dioxide, low temperatures, heat-shock and drought), produces highly reactive free radicals at the surface of plant cell membranes (Nieto-Sotelo & Ho, 1986;Alscher & Amthor, 1988;Heath & Castillo 1988). Among the deleterious effects caused by prolonged exposure to ozone, the most noticeable at the plant level are leaf chlorosis and accelerated senescence (Reich & Lassoie, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…destruction of H,O, in chloroplasts, in the detoxification of xenobiotics (Rennenberg, 1982;Edwards and Owen, 1986;Martinoia et al, 1993), and in protection against various stresses, such as irradiation (Meister and Anderson, 1983), heat (Nieto-Sotelo and Ho, 1986), oxidative stress dueto O, or SO, (Alscher, 1989), and exposure to heavy metals (Grill et al, 1985). Supply of GSH to suspension-cultured cells of bean stimulates the transcription of various defense genes, including those encoding cell wall Hyp-rich glycoproteins, phenylalanyl ammonia-lyase, and chalcone synthase (Wingate et al, 1988).…”
mentioning
confidence: 99%